(untitled) (BIRDEM Medical Journal, 2023)
Background: Carpal tunnel syndrome (CTS) is the most common compression neuropathy in the upper limb in general population. Female gender, obesity, increase of age, diabetes mellitus (DM), hypothyroidism, pregnancy, rheumatoid arthritis, osteoarthritis and occupational factors like repetitive work are the main risk factors for CTS. The objective of this study was to determine whether the nerve conduction study measurement of the median nerve (MN) at the wrist differ between diabetic and non-diabetic CTS patients. Methods: This cross-sectional study was conducted at Electrodiagnostic Lab of BIRDEM General Hospital and Popular Medical College Hospital, Dhaka during the period of October 2017 to August 2019. Five hundred and seventeen hands from 377 patients were sampled according to inclusion criteria. Participants were assigned to two groups: Group 1 (CTS with DM) and Group 2 (CTS without DM). NCS study were performed using Nihon Kohden electrodiagnostic machine. Measurements at the MN was taken under consideration for study. Severity of CTS was graded according to Canterbury electrophysiologic grading scale and parameters were compared among diabetic and non-diabetic participants. Data were analyzed using Statistical Package for the Social Sciences SPSS version 23 (SPSS Inc., Chicago, IL, USA). Results: The 377 participants comprised 144 and 233 in Group 1 and Group 2, respectively. Out of 377 patients, 334 (88.59%) were females and there was no statistically significant difference between two groups. The average age was 50.66±10.2 years in diabetic participants and 43.34±10.7 years in non- diabetic participants. In the study population moderate CTS (Grade 3) was the most frequent (46.4%) followed by very severe (Grade 5) CTS. There was no statistically significant difference in incidence between diabetic and non-diabetic patients. Analysis of electrophysologic parameters of MN showed statistically significant difference in mean MN sensory nerve action potential (SNAP) amplitude (P 0.003), compound muscle action potential (CMAP) amplitude (p 0.05, right) and CMAP latency (p 0.02, right and 0.05, left) between diabetic and non –diabetic patients. Inter-group comparison revealed that impaired glycaemic status and duration of diabetes in diabetic population had a minimal influence in the electrophysiological severity of CTS in either hands. Conclusion: Some nerve conduction study parameters of the MN differ significantly between diabetic and non-diabetic patients with CTS and may provide both diagnostic and predictive results across the entire spectrum of CTS. BIRDEM Med J 2023; 13(3): 136-142